A emergência do campo artístico em Belo Horizonte: décadas de 20 e 30 - Joao Ivo D M Pinheiro Duarte Guimaraes (2011)
The world of plastic arts in Belo Horizonte in the early 20th century is typically characterised as inherently precarious, traditional and academic. This essay investigates this period and environment, using as a focal point the essential figure of Aníbal Mattos, and questions the validity of this recurrent characterization. This essay asserts that Mattos role inthe incentivation and articulation of the artistic environment in Belo Horizonte was decisive, so much so that the emphases of this article also incorporates some observations of his personal and institutional trajectory in the intellectual and artistic environment of the time.Within this article it is argued that Aníbal Mattos should be seen as a dynamic individual, fundamental to the integration of artists and other interested parties, by promoting exhibitions and education institutions, even if only short lived. This characterization of Mattos as an articulator of such relevance raises doubts concerning certain common assumptions about the artists actions towards the modernist movement, as well as the popularly perceived duality between academicism and modernism.